Potential primary roles of glial cells in the mechanisms of psychiatric disorders - Yamamuro, Kazuhiko; Kimoto, Sohei; Rosen, Kenneth M.; Kishimoto, Toshifumi; Makinodan, Manabu (Frontiers in Cellular Neuroscience, 2015)
While neurons have long been considered the major player in multiple brain functions such as perception, emotion and memory, glial cells have been relegated to a far lesser position, acting as merely a “glue” to support neurons. Multiple lines of recent evidence however, have revealed that glial cells such as oligodendrocytes, astrocytes and microglia, substantially impact on neuronal function and activities and are significantly involved in the underlying pathobiology of psychiatric disorders. Indeed, a growing body of evidence indicates that glial cells interact extensively with neurons both chemically (e.g. through neurotransmitters, neurotrophic factors and cytokines) and physically (e.g. through gap junctions), supporting a role for these cells as likely significant modifiers not only of neural function in brain development but also disease pathobiology. Since questions have lingered as to whether glial dysfunction plays a primary role in the biology of neuropsychiatric disorders or a role related solely to their support of neuronal physiology in these diseases, informative and predictive animal models have been developed over the last decade. In this article, we review recent findings uncovered using glia-specific genetically modified mice with which we can evaluate both the causation of glia dysfunction and its potential role in neuropsychiatric disorders such as autism and schizophrenia.